2016
DOI: 10.1021/jacs.5b13386
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Two-Electron Transfer in a CdS Quantum Dot–Extended-Viologen Cyclophane Complex

Abstract: Time-resolved optical spectroscopies reveal multielectron transfer from the biexcitonic state of a CdS quantum dot to an adsorbed tetracationic compound cyclobis(4,4'-(1,4-phenylene) bipyridin-1-ium-1,4-phenylene-bis(methylene)) (ExBox(4+)) to form both the ExBox(3+•) and the doubly reduced ExBox(2(+•)) states from a single laser pulse. Electron transfer in the single-exciton regime occurs in 1 ps. At higher excitation powers the second electron transfer takes ∼5 ps, which leads to a mixture of redox states of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 42 publications
1
45
0
Order By: Relevance
“…Since the initial report by Wasielewski and co-workers in 1992, 14 a few molecular systems have been reported that photoaccumulate reducing equivalents. 15 17 The electron storage sites range from organic structures such as naphthalene or perylene bisimides, 14 , 18 anthraquinone, 19 and viologen derivatives, 20 , 21 to iridium( iii ) 22 or rhodium( iii ) 23 complexes and polyoxometalates. 24 , 25 Ruthenium complexes containing NAD(P) + /NAD(P)H mimics were also elegantly developed by the group of Tanaka.…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial report by Wasielewski and co-workers in 1992, 14 a few molecular systems have been reported that photoaccumulate reducing equivalents. 15 17 The electron storage sites range from organic structures such as naphthalene or perylene bisimides, 14 , 18 anthraquinone, 19 and viologen derivatives, 20 , 21 to iridium( iii ) 22 or rhodium( iii ) 23 complexes and polyoxometalates. 24 , 25 Ruthenium complexes containing NAD(P) + /NAD(P)H mimics were also elegantly developed by the group of Tanaka.…”
Section: Introductionmentioning
confidence: 99%
“…Charge separation dynamics with the use of various electron acceptors has been reported in many papers. [5][6][7][8][9][10][11][12][13][14][15][16][17] For example Banin et al reported that hybrid nanostructures of Au-tipped CdS nanorods with a larger Au size exhibited a higher probability for charge separation of multiple excitons formed in the CdS nanocrystals, improving the photocatalytic activity for H 2 generation. 15 The rate of photoinduced electron transfer from CdSe NCs to methyl viologen (MV 2+ ) was shown to be dependent on the particle morphology: plate-like CdSe NCs exhibited a slower rate than that of spherical or rod-shaped CdSe NCs due to the weak electronic coupling along the short and long axes in the lateral dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Solution samples were prepared in 2 mm path length glass cuvettes and degassed with three freeze‐pump‐thaw cycles. The TA data were subjected to global kinetic analysis to obtain the evolution‐ and decay‐associated spectra and kinetic parameters as described in detail previously …”
Section: Methodsmentioning
confidence: 99%
“…The TA data were subjected to global kinetic analysis to obtain the evolution-and decayassociated spectra and kinetic parameters as described in detail previously. [20]…”
Section: Transient Absorption Spectroscopy and Global Analysismentioning
confidence: 99%